Unexpected 13N concentrations in ISIS synchrotron room air. (April 2022) - Jones, B.; Burns, G.J.; Cavanagh, H.V.; Findlay, D.J.S.; Karbassi, S.; Nilsson, N.A.; Škoro, G.P.; Wright, P.N.M.
Abstract: The specific activity of air in the large open room housing the 800-MeV proton synchrotron of the ISIS Spallation Neutron and Muon Source has been measured. Air from several positions within the ISIS synchrotron room was sucked through a long flexible tube, and run past a shielded HPGe gamma-ray detector outside the synchrotron room. In spite of an expectation that 13 N should be the largest component of the overall activity in the air, the results of the measurements are consistent with the presence in the air of 11 C and 41 Ar only, and suggest that the activity in the air is mostly created not in the synchrotron room itself but in the massive shielding monoliths around the neutron-producing targets, monoliths through which ventilation air is drawn into the synchrotron room. Typical specific activities of 11 C and 41 Ar in the air in the synchrotron room are ∼0.10 and ∼0.03 Bq cm –3 respectively, the upper limit for 13 N being at most ∼0.01 Bq cm –3 . Highlights: Measurement of activity of air in ∼200-kW 800-MeV proton synchrotron room. Air drawn past remote shielded HPGe gamma-ray detector. Measurement programme spanned 2 years. Unexpectedly low concentrations of 13N found.